El desarrollo de la distinción percepción-fantasía en la fenomenología de Edmund Husserl. Repensando las limitaciones del período previo a 1904/5 - Guerrero Cordero, Felipe Iván (Pontificia Universidad Católica del Perú, 2025)
This paper has a dual objective. On the one hand, it aims to reconstruct the challenges Husserl encountered in his attempt to conceptualize phantasy and perception during the pre-1904/1905 period. On the other hand, it proposes the following hypothesis: whereas it is well-established that the schemes of image-thing (Bild-Sache) and act-content are inadequate for a precise conceptualization of the experience of phantasy, two concepts enable a more accurate description: the idea of reproduction and the notion of indication (Anhalt) of being. The latter concept emerges in the Allgemeine Erkenntnistheorie Vorlesung of 1902/1903. By examining these issues, we gain insight into both the limitations and strengths of the image-thing and the act-content of apprehension models, particularly regarding the relationship between perception and phantasy.

Este trabajo tiene un doble objetivo. Por una parte, busca reconstituir los problemas a los cuales Husserl se vio enfrentado en su intento por conceptualizar la fantasía y la percepción en su período previo a 1904/5. Por otro lado, busca sostener la siguiente hipótesis: si bien es consabido que, desde el esquema imagen-cosa (Bild-Sache) y del esquema acto-contenido de la aprehensión, no era posible una conceptualización precisa de la experiencia de fantasía, hay, sin embargo, dos ideas que permiten una descripción más justa, a saber, la de reproducción y la de indicio (Anhalt) de ser. Esta última aparece en la Allgemeine Erkenntnistheorie Vorlesung de 1902/3. Esto permitirá ver las limitaciones y virtudes tanto del modelo de la imagen-cosa, como del modelo acto-contenido de la aprehensión en torno al problema de la relación percepción-fantasía.
The Development of the Distinction between Perception and Phantasy in Husserl’s Phenomenology: Rethinking the Limitations of the pre-1904/5 period
Keywords: Husserl; Perception; Phantasy; Image; Apprehension; Husserl; Percepción; Fantasía; Imagen; Aprehensión; https://purl.org/pe-repo/ocde/ford#6.03.01